The Use of Hibiscus sabdariffa L. in human health, its chemical, nutritional and functional characteristics. A bibliographical review - Brasil, Luciane do Socorro Nunes dos Santos; Costa, Ana Jéssica da Silva; Brasil, Davi do Socorro Barros; Lopes, Alessandra Santos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Hibiscus sabdariffa L. was introduced to Brazil for the production of wines and vinegars and is now known as an unconventional food plant. It has chemical and nutritional potential due to its antioxidant properties and its representative value of anthocyanins, vitamin C and polyphenols. The aim of this research was to carry out a systematic review with a qualitative narrative analysis of studies in the literature on the chemical, functional and nutritional knowledge of vinagreira. The methodology used a qualitative narrative analysis of studies published in journals indexed in the Google Scholar, Science Direct, Scielo and PubMed databases. Articles published up to 2023 were included. The advantages and difficulties of using this raw food material were addressed. The results found from 2000 to 2023 show that Hibiscus sabdariffa L. has a large number of benefits associated with this species, identifying that the aqueous and ethanolic extracts made mainly from the calyx of the plant are very promising and can be used efficiently to compose food products or in other industries such as pharmaceuticals and cosmetics to make different formulations that can be used for the benefit of the world's population. It can be concluded that vinagreira is a plant used for medicinal purposes, with a functional property claim, which could be an important aid in the nutritional balance of the diet plan of patients with comorbidities such as obesity, dyslipidemia, hypertension and some types of cancer, possessing therapeutic properties such as diuretic, analgesic, antihypertensive and antioxidant effects.
Keywords: Hibiscus; Amazon; antioxidant